CONSTITUTIONAL AND LEGAL REGULATION OF SOCIAL RELATIONS - Zhanna Amangeldinovna Хамзина; Yermek Abiltayevich Бурибаев; Adlet Toktamisovich Ермеков (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
This work studies the problems in determining the social sphere as an object of constitutional regulation, constitutional institution, as well as specific sphere of social relations, in which the mechanism of guarantee for constitutional social rights is realized. It was concluded that the content of constitutional and legal institution of social sphere is revealed through cross-sector analysis of legal norms of its components, and interdisciplinary study of elements of its structure. These methodological approaches are ensured by the fact that the system of constitutional right is inherent in being dominant with respect to the Kazakh law system, comprehensive property of constitutional norms; these approaches are realized, embodied and concretized in norms that make up other legal spheres in legislation